The Potential of Ozone/UV System in The Treatment of Batik Wastewater in Indonesia - Chris Salim; Maria Prihandrijanti (Journal of Applied Science and Advanced Engineering, 2023)
The Batik dyeing method, producing famous fabric products recognized locally and internationally, requires lots of wax and dyes in the dyeing process. The wastewater containing high loads of organic pollutants requires proper treatment to prevent environmental damage. Among many technologies developed for wastewater treatment, combining ozonation and UV irradiation has been a promising method due to its effectiveness in degrading and reducing the organic pollutants in wastewater. In this study, Batik wastewater was treated using commercially available ozone generators and UV lamps in a combined ozone/UV system to confirm the effectiveness and to propose a simple and economically feasible method for Batik wastewater treatment. The color and the suspended solids in the wastewater were reduced significantly after 48-hour treatment using the setup in this study. A simple simulation of the investment and operational costs was also conducted.